2016
DOI: 10.1016/j.neurobiolaging.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Regional expression of the MAPT gene is associated with loss of hubs in brain networks and cognitive impairment in Parkinson disease and progressive supranuclear palsy

Abstract: Abnormalities of tau protein are central to the pathogenesis of progressive supranuclear palsy, whereas haplotype variation of the tau gene MAPT influences the risk of Parkinson disease and Parkinson's disease dementia. We assessed whether regional MAPT expression might be associated with selective vulnerability of global brain networks to neurodegenerative pathology. Using task-free functional magnetic resonance imaging in progressive supranuclear palsy, Parkinson disease, and healthy subjects (n = 128), we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 46 publications
2
75
0
Order By: Relevance
“…In agreement with our study, a previous analysis involving the ADNI cohort also found that baseline levels of CSF α -synuclein were not correlated to atrophy brain rates across the spectrum of normal aging, MCI, and AD (Mattsson et al., 2013). These findings, considered together with autopsy-confirmed reports of relatively preserved brain structure in Lewy body diseases (Nedelska et al., 2015), suggest that the effects of α -synuclein pathology may be mediated via cellular dysfunction and functional network disruption (Peraza et al., 2015, Rittman et al., 2016). These are important questions that will be further addressed by the future development of PET radioligands for α -synuclein (Eberling et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our study, a previous analysis involving the ADNI cohort also found that baseline levels of CSF α -synuclein were not correlated to atrophy brain rates across the spectrum of normal aging, MCI, and AD (Mattsson et al., 2013). These findings, considered together with autopsy-confirmed reports of relatively preserved brain structure in Lewy body diseases (Nedelska et al., 2015), suggest that the effects of α -synuclein pathology may be mediated via cellular dysfunction and functional network disruption (Peraza et al., 2015, Rittman et al., 2016). These are important questions that will be further addressed by the future development of PET radioligands for α -synuclein (Eberling et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MR modalities that demonstrate abnormalities in PSP‐RS include magnetic resonance spectroscopy and magnetization transfer imaging, although the ability of these modalities to differentiate PSP‐RS from other parkinsonian disorders is unclear . Resting‐state (task‐free) functional MRI has also been used to demonstrate abnormalities in functional connectivity in PSP‐RS across the network of PSP‐RS‐associated regions, but the loss of cortical connectivity is not specific to PSP‐RS versus PD . Longitudinal MR studies have shown increased rates of whole‐brain, cortical, and midbrain atrophy and SCP diffusivity in PSP‐RS compared with controls, with some evidence for greater rates than in PD, but similar rates of whole‐brain and midbrain atrophy as in MSA‐P .…”
Section: Other Biomarkersmentioning
confidence: 99%
“…181,184,185,205 Resting-state (task-free) functional MRI has also been used to demonstrate abnormalities in functional connectivity in PSP-RS across the network of PSP-RS-associated regions, 63,206,207 but the loss of cortical connectivity is not specific to PSP-RS versus PD. 208 Longitudinal MR studies have shown increased rates of whole-brain, cortical, and midbrain atrophy and SCP diffusivity in PSP-RS compared with controls, [209][210][211][212][213][214][215][216][217][218] with some evidence for greater rates than in PD, but similar rates of whole-brain and midbrain atrophy as in MSA-P. 212,215 However, cortical and whole-brain rates of atrophy are greater in CBS than in PSP-RS. 209,213 Cerebral blood flow single-photon emission computed tomography studies have demonstrated frontal [219][220][221][222][223][224][225] and, less commonly, thalamic 220 and striatal 222 hypoperfusion in PSP-RS.…”
Section: Other Biomarkersmentioning
confidence: 99%
“…Reduced functional activity was found in the contralateral caudate, primary motor and premotor cortex, and ipsilateral putamen in PSP when compared with PD . Highly connected cortical regions suffered a disproportionate loss of FC in PSP, which correlated with the regional expression of the gene MAPT . Specific changes in the connectivity of the dorsal midbrain and striatum also occurred in PSP, including corticostriatal connections that correlated with disease severity .…”
Section: High‐field Mri Of Parkinsonism and Its Progressionmentioning
confidence: 92%
“…181 Highly connected cortical regions suffered a disproportionate loss of FC in PSP, which correlated with the regional expression of the gene MAPT. 182 Specific changes in the connectivity of the dorsal midbrain and striatum also occurred in PSP, including corticostriatal connections that correlated with disease severity. 181,183 These results suggest that the magnitude and topology of functional brain networks is changed by PD, PSP, and MSA.…”
Section: R I I N P a R K I N S O N I A N D I S O R D E R Smentioning
confidence: 99%